Association study between SNP markers located in meat quality candidate genes with intramuscular fat content in an endangered dual-purpose cattle population - Halli, Kathrin; König, Sven; Giambra, Isabella J; Justus Liebig University Giessen (My University, 2024)
The aim of this study was to associate single nucleotide polymorphisms (SNP) of the bovine calcium-activated neutral protease µ-calpain, calpastatin, diacylglycerol-O-acyltransferase, adipose fatty acid binding protein, retinoic acid receptor-related orphan receptor C (RORC), and thyroglobulin (TG) gene with intramuscular fat content (IMF). Therefore, 542 animals of the cattle breed “Rotes Höhenvieh” (RHV) were phenotyped for IMF. Genotyping of the animals was performed using polymerase chain reaction-restriction fragment length polymorphism tests for six SNP from candidate genes for meat quality traits. In addition, we calculated allele substitution and dominance effects on IMF. A subgroup of animals (n = 44, reduced dataset) with extraordinary high IMF was analyzed separately. The mean IMF content was 2.5% (SD: 2.8) but ranged from 0.02% to 23.9%, underlining the breeds’ potential for quality meat production. Allele and genotype frequencies for all SNP were similar in the complete and reduced dataset. Association analyses in the complete dataset revealed the strongest effects of RORC on IMF (P = 0.075). The log-transformed least-squares mean for IMF of genotype g.3290GG was 0.45 ± 0.16, 0.26 ± 0.14 for genotype g.3290GT, and 0.32 ± 0.14 for genotype g.3290TT. In the reduced dataset, we found a significant effect (P < 0.05) of the g.422C>T-SNP of TG on IMF, with highest IMF for genotype CT (0.91 ± 0.17), lowest IMF for genotype TT (0.37 ± 0.25), and medium IMF for genotype CC (0.59 ± 0.16; log-transformed values). Compared to the complete dataset, allele substitution effects increased in the reduced dataset for most of the SNP, possibly due to the selective genotyping strategy, with focus on animals with highest IMF implying strong phenotypic IMF contrast. Dominance effects were small in both datasets, related to the high heritability of IMF. Results indicated RHV breed particularities regarding the effects of meat quality genes on IMF. An explanation might be the breeding history of RHV with focus on adaptation and resilience in harsh outdoor systems. Consequently, it is imperative to develop breed-specific selection strategies. Allele substitution and dominance effects were in a similar direction in both datasets, suggesting the same breeding approaches for different RHV strains in different regions. Nevertheless, a selective genotyping approach (reduced dataset), contributed to more pronounced genotype effect differences on IMF and dominance values.
Keywords: ddc:640; ddc:360